Gambaran Tingkat Stress Mahasiswa S1 Keperawatan Universitas Muhammadiyah Purwokerto Selama Menjalani Praktek Klinik Keperawatan Dasar - Anisatul Farodisa; Kris Linggardini (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Stress is a body's response that is not specific to any demands or burdens. Stress may occur in students who had the clinical practice for the first time because the changes in students' learning conditions from safe and comfortable conditions to an environment is completely new for them. In addition, most of the students are not familiar with the environment in the venue of the clinical practice which requires them to make adjustments to these conditions so that it does not endanger their well-being.Objective: To determine the stress level of nursing students while undergoing basic nursing clinical practice.Method: This study used a quantitative descriptive method through a cross sectional approach. The sampling technique used in this research was cluster random sampling with a sample size of 169 respondents that matched the inclusion and exclusion criteria. The questionnaire used in this study was PSS (Perceived Stress Scale).Results: The results of this research showed that the majority of respondents were 19 years old. There were 106 respondents aged 19 years old (62.7%). Furthermore, the majority of respondents was female with 134 female respondents (79.3%). The stress levels of students in basic nursing practice were mostly in the moderate category with 96 (56.8%), mild stress with 70 (41.4%), and severe stress with 3 (1.8%).Conclusion: Stress levels of students who practice basic nursing clinics are mostly in the moderate category.Keywords: Students, clinical practice, basic nursing.